Institutional legitimacy in Sub-Saharan Africa. Issue 7 (3rd October 2019) - Dreier, Sarah K.; Lake, Milli
ABSTRACT: How do personal encounters with legal institutions shape citizens' confidence in those institutions throughout sub-Saharan Africa? Using Afrobarometer's cross-national citizen survey, we show that negative first-hand experiences with government courts and police erode citizens' trust in those state institutions but do not tend to disrupt citizens' perceptions of their authority to arbitrate or enforce the law. Individuals from diverse demographic backgrounds imbue state institutions with the right to perform their governance and law-enforcement duties, even after experiencing institutional incompetence or injustice. This article advances existing comparative research on legal institutions, which tends to conflate trust and legitimacy and overlooks the distinction between de facto performance and de jure authority. We suggest that rule-of-law institutions have deeper roots than some scholars have previously supposed.